2021
DOI: 10.3390/cancers13246370
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Superselective Conventional Transarterial Chemoembolization Using Guidance Software for Hepatocellular Carcinoma within Three Lesions Smaller Than 3 cm

Abstract: The indication of transarterial chemoembolization (TACE) has advanced to hepatocellular carcinoma (HCC) of Barcelona Clinic Liver Cancer (BCLC) stage A when surgical resection (SR), thermal ablation, and bridging to transplantation are contraindicated; however, TACE for small HCC is frequently difficult and ineffective because of less hypervascularity and the presence of tumor portions receiving a dual blood supply. Here, we report outcomes of superselective conventional TACE (cTACE) for 259 patients with HCCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Many studies have demonstrated efficacy in terms of visualization of artery feeders and reduction of radiation dose in TACE using AFD softwares. 7173…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated efficacy in terms of visualization of artery feeders and reduction of radiation dose in TACE using AFD softwares. 7173…”
Section: Discussionmentioning
confidence: 99%
“…71 Many studies have demonstrated efficacy in terms of visualization of artery feeders and reduction of radiation dose in TACE using AFD softwares. [71][72][73] AI and specifically radiomics, with the extraction of quantitative features from radiological images and the combination of these with clinical and genetic/molecular models, have been improving the prognostic assessment prior to perform both percutaneous and endovascular procedures. [74][75][76][77][78][79] In conclusion, robotic-guidance in IR has demonstrated important benefits for its use, with wide applications in endovascular and percutaneous procedures using CT-, MR-, US-imaging and imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The REFLECT trial established the first-line status of lenvatinib ( 45 ), and Ding et al ( 46 ) demonstrated its superior efficacy compared with sorafenib in HCC combination therapy. Regorafenib and cabozantinib, which are the second-line drugs for advanced HCC, were also approved following the RESORCE and CELESTIAL trials ( 47 , 48 ), With the development of drug-eluting beads and the advancement of super-selective TACE ( 2 , 49 ), further studies are recommended to investigate the efficacy of these new oral drugs in combination with interventional modalities for advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
“…First, it was a retrospectively study. Second, the detail of TACE technique and sequencing were not explored, which could be another factor affecting lower survival outcome (Miyayama et al, 2021). Third, our study was done in one healthcare center.…”
Section: Discussionmentioning
confidence: 99%